Blockchain in Peer-to-Peer Platforms: Enhancing Sustainability and Customer Experience in Tourism. - Prados-Castillo, Juan Francisco; Torrecilla-García, Juan Antonio; Andraz, Georgette; Guaita Martínez, José Manuel (MDPI, 2023)
Blockchain technology is emerging as a high-impact solution for the tourism industry, a topic chosen for its growing research relevance and potential to revolutionise the tourism sector in several areas. This study examines how the combination of Blockchain technology and P2P platforms advances sustainability and marketing in the tourism accommodation market. It attempts to fill a gap in the literature by focusing on its application in two areas, namely digital markets and technology, which are expanding. The originality of this research lies in its comprehensive review of blockchain applications in tourism from a practical point of view, which has been largely unexplored in the existing literature. Through a bibliometric review of forty-two papers, various Blockchain applications were identified, such as improving transparency, trust, and efficiency in hotel operations and eliminating intermediaries to reduce costs. The adoption of smart contracts and the use of cryptocurrencies have also emerged as key trends. These findings highlight the transformative potential of Blockchain technology to build trust between hosts and guests, streamline processes, and improve the customer experience. However, they emphasise the need for the careful planning and consideration of the challenges associated with implementing this technology. Future research should further explore the specific applications of Blockchain technology in tourism to optimise its impact on industry and ensure long-term sustainability.
CC BY
Keywords: Blockchains; Alojamientos turísticos; Marketing en Internet; P2P platforms; Blockchain technology; Tourist accommodation; Marketing advancements; Consumer adoption